"Your Finger or Mine?"—Patient Preferences in the Collection of Fecal Occult Blood Testing in the Emergency Department. Issue 9 (30th June 2020) - Freeman, Paul; Couperus, Kyle; Walsh, Ryan; Ward, Michael J; McNaughton, Candace D; Bothwell, Jason
Abstract: Introduction: There are a number of presenting Emergency Department complaints that may necessitate the testing of stool for the presence of blood. A provider-performed digital rectal examination is frequently performed solely for the collection of stool for a fecal occult blood testing (FOBT). With increased emphasis on patient autonomy and shared decision-making, it is appropriate to consider patient preferences with regard to who performs the invasive collection of stool. Our objective was to determine patient preference in regard to provider versus self-collection of stool sample for use in FOBT and identify patient demographics associated with those more likely to self-collect. Finally, we examined specimen adequacy and patient satisfaction by open-ended comment. Materials and Methods: We conducted a 1-year, prospective, non-randomized, observational trial with a convenience sample of 100 patients. After enrollment, study participants were offered the choice of self-collection versus provider collection. Stool collection proceeded according to participant preference. Simple descriptive statistics were used to analyze the primary outcome. The secondary proportional univariate outcomes were evaluated with chi-square testing (alpha level—0.05). We used a multivariable logistic regression model to evaluate the association of independent variables with the likelihood to perform self-collection. Results: A total of 100 patients were enrolled over 1 year, with 51% choosing to collect their own sample. Younger age was the only statistically significant predictor for self-collection ( p < 0.001); furthermore, for every year of increasing age, patients were 3% less likely to choose self-collection. All self-collected samples were adequate for testing. In univariate analyses, patients younger than 35 were more likely to perform self-collection (66%) compared with those over 35 (36%). Those over 64 self-collected only 24% of the time. Neither sex nor race were associated with collection method preference. Conclusions: When offered the choice between self-directed or provider-performed stool sample collection, more than half of participants chose to obtain their own sample; furthermore, age was the only statistically significant predictor of preference for collection method. All patients who self-collected were able to provide an adequate sample. Our evidence suggests the offer of FOBT self-collection is a feasible method to enhance patient autonomy and improve therapeutic alliances.